1974
DOI: 10.1161/01.cir.49.5.870
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Recognition of the Congenital Bicuspid Aortic Valve

Abstract: SUMMARYTwenty-one patients (age four to 25 years) with bicuspid aortic valves proved by surgery and angiography (12) or angiography alone (9) were studied by echocardiography. Seventeen patients had aortic valve disease (11 stenosis, 6 incompetence) and four had coarctation of the aorta with normally functioning aortic valves. A comparison group of 16 patients (9 with aortic valve disease and 7 without aortic valve disease) who had proven tricuspid aortic valves was also studied. Echocardiograms in tricuspid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Although those studies have demonstrated the sensitivity of leaflet tissue to WSS magnitude and pulsatility, the elucidation of the role played by native BAV WSS abnormalities in CAVD pathogenesis has been hampered by the complexity of the native BAV hemodynamic environment and the challenge to replicate it in the laboratory setting. BAV flow visualization [49], radiography [50], [51] and magnetic resonance imaging [52][54] have revealed the existence of an elliptical clam-shell shaped orifice, an intrinsic degree of stenosis, an eccentric systolic jet and abnormal downstream helical flow patterns. Our recently published computational work on the comparison of TAV and type-I BAV WSS [55] demonstrated that, while those hemodynamic abnormalities have little impact on the non-coronary BAV leaflet WSS, they significantly affect the pulsatility and magnitude of the WSS on the fused BAV leaflet, which is interestingly the leaflet most vulnerable to calcification [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although those studies have demonstrated the sensitivity of leaflet tissue to WSS magnitude and pulsatility, the elucidation of the role played by native BAV WSS abnormalities in CAVD pathogenesis has been hampered by the complexity of the native BAV hemodynamic environment and the challenge to replicate it in the laboratory setting. BAV flow visualization [49], radiography [50], [51] and magnetic resonance imaging [52][54] have revealed the existence of an elliptical clam-shell shaped orifice, an intrinsic degree of stenosis, an eccentric systolic jet and abnormal downstream helical flow patterns. Our recently published computational work on the comparison of TAV and type-I BAV WSS [55] demonstrated that, while those hemodynamic abnormalities have little impact on the non-coronary BAV leaflet WSS, they significantly affect the pulsatility and magnitude of the WSS on the fused BAV leaflet, which is interestingly the leaflet most vulnerable to calcification [2].…”
Section: Introductionmentioning
confidence: 99%
“…The features of BAV on a TTE include systolic doming, an eccentric closure line in the parasternal long axis views, presence of a single commissural line in the diastolic phase with the occurrence of two cusps and the occurrence of two commisures in the parasternal short axis views [ figure 4] [59,60].…”
Section: Echocardiographymentioning
confidence: 99%
“…Echocardiography was performed using a Smith Kline Ekoline sector scanner and a 2. 25 MHz transducer in a standard manner as previously described." Multiple diastolic aortic root echoes were defined as three or more linear parallel echoes in the root as reported by Gramiak and Shah.12 A typical M-mode echocardiogram in a patient with increased diastolic echoes is seen in Fig.…”
Section: M-mode Echocardiographymentioning
confidence: 99%